2018
DOI: 10.1111/jen.12593
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide‐ and temperature‐mediated changes in plant defensive compounds alter food utilization of herbivores

Abstract: Although the impact of elevated carbon dioxide and rising temperature on plants and animals has been extensively documented recently, only limited understanding exists regarding their combined effects. The objective of this research was to address the consequences of using combinations of elevated CO2 and elevated temperature on a plant's defensive chemistry, and subsequent utilization of the plant as insect food. Our results indicated that elevated CO2 and increased temperature, for the most part, act indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…According to the report published by the National Oceanic and Atmospheric Administration (NOAA), the atmospheric CO 2 concentration increased by nearly 10 ppm in the past five years, and it was still growing continuously [ 1 ], and was predicted to reach 800 ppm by the end of the 21st century [ 2 ]. As a raw material for photosynthesis, elevated CO 2 can directly affect the photosynthetic rate of plants [ 3 ], further affect the C/N ratio of plant tissues [ 4 , 5 , 6 ], and simultaneously change the allocation of primary and secondary metabolites in plant tissues [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the report published by the National Oceanic and Atmospheric Administration (NOAA), the atmospheric CO 2 concentration increased by nearly 10 ppm in the past five years, and it was still growing continuously [ 1 ], and was predicted to reach 800 ppm by the end of the 21st century [ 2 ]. As a raw material for photosynthesis, elevated CO 2 can directly affect the photosynthetic rate of plants [ 3 ], further affect the C/N ratio of plant tissues [ 4 , 5 , 6 ], and simultaneously change the allocation of primary and secondary metabolites in plant tissues [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the substrate of plant photosynthesis, the change of CO 2 concentration directly affects the photosynthesis and metabolism of plants, especially C 3 plants (Ainsworth & Long, 2005; Ainsworth et al., 2007; Long et al., 2005). The augment of atmosphere CO 2 concentration could improve the photosynthesis efficiency, biomass and carbon‐to‐nitrogen ratio of C 3 plants, which could lead to changes in the contents of primary and second metabolism (Dáder et al., 2016; Lindroth, 2010; Sun et al., 2009; Teawkul & Hwang, 2019; Vassiliadis et al., 2016), then affect the growth and physiological metabolism of insect herbivores fed on them (Paulo et al., 2020; Stacey & Fellowes, 2002; Stiling & Cornelissen, 2007; Trębicki et al., 2017; Zavala et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, an increase in carbon allocation reduces the amount of nitrogen in the plant tissues, thereby reducing the amount of soluble proteins and amino acids (Broberg, Högy, & Pleijel, 2017; Ryan, Emiljanowicz, Härri, & Newman, 2014; Sun, Jing, & Ge, 2009). In addition, these changes may cause alterations in the production of secondary metabolites and plant defences (Bidart‐Bouzat & Imeh‐Nathaniel, 2008; Casteel et al., 2008; Guo et al., 2014; Rajashekar, 2018; Teawkul & Hwang, 2019; Zavala, Nabity, & DeLucia, 2013). Several studies have reported changes in the sugar levels, flavonoids, caffeic acid, total phenolics, antioxidant capacity and jasmonic acid pathway of plants exposed to high concentrations of CO 2 (Becker & Kläring, 2016; Giri, Armstrong, & Rajashekar, 2016; Jin et al., 2015; Li et al., 2019; Moretti, Mattos, Calbo, & Sargent, 2010).…”
Section: Introductionmentioning
confidence: 99%